EMPOWERING MSMEs THROUGH SOYBEAN PULP-BASED SUPPLEMENTARY FOOD INNOVATION TO PREVENT STUNTING IN BANTENGAN VILLAGE, MADIUN - Afiva Tria Sandrina; Andini Maulidiyah Rachma; Cindashany Prijantika; Vemmy Zulfia Widyan; Dilla Jandini Airsyahani; Intan Taniya; Siti Nabilah; Faberian Diantama; Juan Prakoso Irawan; Anisa Lailatul Fitria, S.Gz, M.Sc (Universitas Airlangga, 2026)
Chronic nutritional problems such as stunting remain a challenge in Indonesia, including in Bantengan Village, Wungu District, Madiun Regency, where there are 16 stunting cases and low exclusive breastfeeding coverage. To address the problems, the community service team conducted a socialization and demonstration of an innovative Supplementary Feeding (PMT) program using soybean pulp as the basic ingredient, which has long been considered as waste. The socialization covered stunting prevention strategies, the importance of exclusive breastfeeding, and the nutritional value of soybean pulp. The demonstration showed how to process soybean pulp into NugSoy, a child-friendly PMT product. The program aimed to increase the knowledge of the community, especially integrated health post cadres and MSME actors, about the potential of soybean pulp as a nutritious PMT ingredient. The N-Gain method was used to evaluate the increase in participants' knowledge, and the results showed an average score of 0.76 (high category) with a percentage of 76.73%, indicating a significant increase in knowledge. The overall participant satisfaction evaluation also showed very satisfying results, although there is room for improvement in the clarity of the material, product taste, and participant motivation. For sustainability, the team documented the activities and created a NugSoy recipe brochure to be handed out to participants, and uploaded a video to an accessible YouTube platform to expand the program's reach.